One new and three known species of Geocenamus Thorne & Malek, 1968 (Nematoda: Merliniidae) from Iran - Ghaderi, Reza; Karegar, Akbar (Zootaxa, 2016)
Soil samples collected from different plants and localities in Iran yielded one new and three known species of the genus Geocenamus with tessellated cuticle. Geocenamus conicaudatus n. sp. is characterised by a hemispherical cephalic region, set-off from the rest of body by a constriction, a slender stylet 17–20 µm long with laterally directed knobs, coarsely annulated cuticle with 32–34 longitudinal striae and a conical tail with smooth, finely rounded terminus. Morphological and molecular studies on the populations of G. paniculoides and G. tartuensis indicated that G. paniculoides may be considered as a valid species. Intraspecific variability of some characters of 30 Iranian populations of G. rugosus were studied. An identification key to 32 valid species of the genus Geocenamus is given.